Inductive methodology and case study for selection of cutting parameters in micromilling of Inconel 718 - Barros, Henrique Hansen; Silva, Gabriel de Paiva; Malcher, Lucival; Oliveira, Déborah de (Brazilian Journal of Production Engineering, 2024)
Manufacturing processes have been increasingly innovated to allow the fabrication of miniaturized parts with high levels of dimensional precision. The main difference between micromachining and conventional machining is size effect, which is due to the similar dimensions of the tool edge radius and the minimum chip thickness. Because of size effect, chip formation is more difficult, resulting in high specific cutting energy and poor surface quality. Thus, in micromachining processes, the adequate choice of cutting parameters is fundamental to enable chip formation. Inconel 718 is nickel-based superalloy that is often used in harsh environments because of its high strength and corrosion resistance. However, this material is widely known for its low machinability. Considering the difficulties associated with micromilling of hard-to-cut alloys, a study on the influence of different cutting parameters on output variables in micromilling of Inconel 718 has been conducted. By means of inductive methodology, case studies and bibliographic review, this work aims to determine the most efficient cutting parameters, tool materials and lubrication conditions in micromilling of Inconel 718. The determination of optimized cutting parameters considers the lowest tool wear rates and minimum burr formation.